2017
DOI: 10.25165/j.ijabe.20171006.3407
|View full text |Cite
|
Sign up to set email alerts
|

Influences of greenhouse-integrated semi-transparent photovoltaics on microclimate and lettuce growth

Abstract: Shading in greenhouses is a simple and cheap method usually used to reduce the intensity of solar radiation and air temperature. Moreover, combining Photovoltaic (PV) panels and crops on the same cropland could alleviate the increasing competition for the agricultural land between food and energy production. In addition, the integration of PV with greenhouses could reduce, or partially replace the energy consumption for greenhouse crop production. Therefore, the aim of this study was to investigate the shading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The other issue is the effect of PVs on the internal microclimate and productivity of the greenhouse. The integration of semitransparent PV panels placed at a distance of 8 cm from the greenhouse pitched roof, covering 20% of the roof, causes solar radiation reduction of 35%-40% and a temperature reduction of 1-3 • C according to field measurements for tomato and lettuce crops [1,7]. In [8], the replacement of the 50% of a pitched roof with multi-crystalline PV measuring the temperature and the solar radiation inside the greenhouse is examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other issue is the effect of PVs on the internal microclimate and productivity of the greenhouse. The integration of semitransparent PV panels placed at a distance of 8 cm from the greenhouse pitched roof, covering 20% of the roof, causes solar radiation reduction of 35%-40% and a temperature reduction of 1-3 • C according to field measurements for tomato and lettuce crops [1,7]. In [8], the replacement of the 50% of a pitched roof with multi-crystalline PV measuring the temperature and the solar radiation inside the greenhouse is examined.…”
Section: Introductionmentioning
confidence: 99%
“…With field measurements the influence of roof integrated PVs on the evapotranspiration rate, and consequently on water management, is also approached [9]. Finally, the effect of the PV incorporation on the roof depends on the percentage of cover but also on the cultivation with tomato and lettuce being less vulnerable than onion [1,3,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The integration of semi-transparent photovoltaic panels can decrease the solar irradiation and the internal air temperatures, as well as generate electric energy for environmental control systems (Hassanien et al [4]).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, appropriate levels of shading and electricity generation can be achieved concurrently. For example, some reported studies have demonstrated that Welsh onion [28], tomato [29,30], lettuce [31][32][33][34], and wild rocket [35] were cultivated properly under the semi-transparent PV panels. Accordingly, solar-radiation use efficiency in the greenhouse would be increased by the use of PV-generated electrical energy for cultivation environment management.Another concept related to the use of PVs in greenhouse roofs is partitioning of the wavelength ranges of the solar radiation spectrum for electrical energy generation and crop cultivation using infrared reflective film [36,37], organic PV cells [38][39][40], dye-sensitized PV cells [41,42], or dichroitic polymer film [43].…”
mentioning
confidence: 99%
“…In this way, appropriate levels of shading and electricity generation can be achieved concurrently. For example, some reported studies have demonstrated that Welsh onion [28], tomato [29,30], lettuce [31][32][33][34], and wild rocket [35] were cultivated properly under the semi-transparent PV panels. Accordingly, solar-radiation use efficiency in the greenhouse would be increased by the use of PV-generated electrical energy for cultivation environment management.…”
mentioning
confidence: 99%